Pendekatan Teori Fractal untuk Menentukan Kurva Retensi Air pada Vertisol dan Alfisol Hasil Olah Tanah - Wirosoedarmo, Ruslan (Jurnal Teknologi Pertanian, 2004)
The water retention in the soil is determined by distribution of soil particle measurement.  The growth of the plants are influenced by the soil characters such as the structure, strength of the soil it self, the soil resitance to water The retention of the water can be estimated exactly by using the distribution data of particle measurement. So far, the determination of the water retention curve used is by using pressure plate, which is set in any pF, so it needs longer time. Model of the water retention characteristic is based on fractal model of soil structure. Up to now, soil structure is difficult to be quantitative or on the other hand, it is stated in qualitative, but by using fractal theory of soil structure, it can be quantitative. Fractal approach to set the water retention characteristic is based on water structure named Pore Solid Fractal (PSF). The model shows water retention characteristic related on water structure parameter, which means not only use the distribution of soil solid measurement related with model scaling. The calculation results using mass and measure are obtained the value of fractal mass dimension (Dm) which is estimated for alfisol = 2.555 ± 0.454, alluvial soil = 2.403 ± 0.332  and vertisol = 2.624 ± 0.419.  The corve of water resistance model is obtained in good result for alfisol with D value of 2.71, alluvial soil with D value of 2.735, and vertisol with D value of 2.878.  Based on the mechanical soil analysis, it could get the alfisol volume weight = 1.248 gr/cm2, alluvial soil = 1.107 gr/cm2, and vertisol = 2.63 gr/cm2, alfisol specific weigt = 2.915 gr/cm3, alluvial soil = 2.42 gr/cm3, and vertisol 2.63 gr/cm3, and alfisol porosity = 0.487m3/m3, alluvial soil = 0.501 m3/m3 and vertisol 0.605 m3/m3 Vertisol has the biggest D value, while alfisol has the smallest one.  Vertisol has the biggest water composition value, while alvisol has the smallest one.  It’s because there is much pliable composition in vertisol.  The D value correlation is in line with the water composition, i.e. the higher of water composition, the higher of D value.   Key Words :  fractal theory, model of soil structure, vertisol, alfisol